The ultimate American pit bull terrier - O'Neil, Jacqueline (New York : Howell Book House, 1995)
Provides information on the history of the American Pit Bull Terrier breed, offers advice on choosing an American Pit Bull as a pet, and discusses training, feeding, health care, and breeding.
108988
Keywords: American pit bull terrier. -- Health; American pit bull terrier. -- Care; American pit bull terrier -- Breeding